Application of IVIM in the assessment of the spleen in patients with myelofibrosis - Bilski, Mateusz; Sobas, Marta; Pawluś, Aleksander; Skarupski, Marek; Zimny, Anna (Frontiers in Oncology, 2026)
AimThe purpose of this study is to investigate whether IVIM-derived spleen parameters including the true diffusion coefficient (D) and perfusion fraction (f) can serve as non-invasive biomarkers to predict fibrotic transformation of the bone marrow.MethodsEighteen patients with MPN and 18 healthy controls (HC) underwent abdominal IVIM diffusion-weighted imaging using 1.5 T MR unit. The values of spleen parameters of D and f were compared between patients with various forms of MPN, including 8 patients with myelofibrosis (MF), 10 patients without myelofibrosis (non-MF) and (HC). A Bayesian approach was adopted in the analysis, to assess whether the D and f coefficients, along with the spleen volume, can predict disease occurrence.ResultsComparing MF patients to HC, Bayesian analysis provided strong evidence for a difference in the f parameter (BF = 18.38), while the difference between MF and non-MF patients was weaker (BF = 1.42). There was no statistically significant difference between non-MF and HC (BF = 0. 64). There was no correlation between f parameter and spleen volume (CI= -0,43; 0,38). Logistic regression analysis with logkit function confirmed that f parameter was significant predictor of MF.ConclusionsThe study demonstrates that IVIM measurements of spleen perfusion in both healthy individuals and MPN patients offer valuable predictive information regarding disease development and progression. The f parameter shows promise for predicting fibrotic transformation of the bone marrow in MPN patients regardless of the size of the spleen.